Gastropods Colour Patterns in Cassiopids and Naticids from Romualdo Formation, Araripe Basin, Northeast Brazil - Pereira, Priscilla Albuquerque; Prado, Ludmila Alves Cadeira do; Araripe, Rilda Verônica Cardoso; Oliveira, David Holanda de; Lemos, Flávia Azevedo Pedrosa; Lobo, Luiz Ricardo da Silva; Tomé, Maria Emília Travassos Rios; Barreto, Alcina Magnólia Franca (Anuário do Instituto de Geociências, 2022)
The phylum Mollusca includes one of the most beautiful examples of colour patterns in present-day shells. However, they are rare in the fossil record because they demand excellent fossilization. In Brazil, colour patterns in fossil mollusk shells are recorded in gastropods Natica aff. bulbulus White, 1887 from the Riachuelo Formation (Aptian-Albian), Sergipe-Alagoas Basin. This paper presents the first gastropod shells from the Romualdo Formation with colour patterns, visible under natural and UV light, belonging to the families Naticidae and Cassiopidae, collected at Santo Antônio outcrop municipality of Exu, Pernambuco and, Pinheiro and Serra do Mãozinha sites, municipality of Missão Velha and Romualdo site, municipality of Crato, Ceará. Among the cassiopids more than 100 specimens were tested, with 1/3 of them showing a residual colour pattern under UV light exposure, after chemical preparation. They correspond to the species Paraglauconia (Diglauconia) araripensis (Beurlen, 1964), Paraglauconia (Diglauconia) lyrica Maury, 1934, Gymnentome (Gymnentome) carregozica (Maury, 1934) and Gymnentome (Gymnentome) romualdoi Beurlen, 1964. The colour pattern is virtually similar in both genera, with fluorescent stripes on a dark background, showing the taxonomic similarity between them. As for the naticids, about 20 specimens were collected and 15 show good preservation, observing the visible colour pattern under natural light in Natica sp. and Euspira sp.; both new taxa for the Araripe Basin. The residual colour pattern in naticids ranges from spiral stripes to sigmoidal lines and blotches of brown and yellowish tones on a paler background, as observed in fossil species of the same family in the Cenozoic. The new occurrences increase the fossiliferous diversity of mollusks of the Romualdo Formation and extend the understanding of the diversity of colouration patterns of Lower Cretaceous gastropods.